First Comprehensive List of Phlebotomine Sand Fly Species (Diptera: Psychodidae) in a Leishmaniasis Focus (Djelfa, Algeria), Including the First Record of Phlebotomus langeroni Females in Algeria - Fatma Messaoudene; Slimane Boukraa; Said Chaouki Boubidi; Ahlem Guerzou (Journal of Arthropod-Borne Diseases)
Background: The wide distribution of phlebotomine vectors complicates the leishmaniasis situation in the world, with the risk of spreading from rural to urban areas. Our study investigates for the first time the ecology and distribution of sand fly populations in leishmaniasis focus (Djelfa, Algeria).